Factors Affecting Private Economic Development in the Context of Economic Institutional Reform in Vietnam: An Empirical Study - Trung, Phan Nhan (Journal of Business Management and Economic Development, 2026)
This study investigates the key factors influencing private economic development (PED) within the context of ongoing economic institutional reform in Vietnam. Grounded in New Institutional Economics, the Resource-Based View, Dynamic Capabilities Theory, and Human Capital Theory, the research proposes and empirically tests a comprehensive framework comprising seven determinants: Institutional Environment (IE), Access to Finance (AF), Digital Transformation (DT), Human Capital Quality (HC), Government Support Policies (GS), Market Competition (MC), and Innovation Capacity (IC). A structured questionnaire was administered to 358 private enterprises across Ho Chi Minh City, Hanoi, Da Nang, and Can Tho, Vietnam. Data analysis was conducted using SPSS 26.0, employing Cronbach's Alpha reliability testing, Exploratory Factor Analysis (EFA), Pearson correlation, and multiple linear regression. The results reveal that six of the seven hypothesized factors significantly and positively affect PED, with Digital Transformation exhibiting the strongest influence (β  = 0.241, p < 0.001), followed by Access to Finance (β  = 0.203), Innovation Capacity (β = 0.196), Institutional Environment (β  = 0.187), Human Capital Quality (β  = 0.168), and Government Support Policies (β  = 0.152). Market Competition was not statistically significant. The model explains 68.3% of the variance in PED (Adjusted R² = 0.677). These findings provide critical evidence for policymakers to prioritize digital infrastructure, financial accessibility, and innovation ecosystems in fostering sustainable private sector growth in Vietnam.